INDIGENOUS KNOWLEDGE OF BUBBOR PADDAS OF SAMBAS COMMUNITY AS EDUCATIONAL VIDEO CONTENT ON BIODIVERSITY VALUE TOPIC - Adinugraha, Fajar; Grace, Mayla; Angelita B, Shezy; Kelana, Kelana (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2024)
The phenomenon of low student knowledge about the value of biodiversity can have an impact on reducing awareness of biodiversity loss. Efforts are made to study biodiversity value related to indigenous knowledge because biodiversity and indigenous knowledge have a close relationship. The indigenous knowledge of the Sambas people, known as Bubbor Paddas, has the potential to educate about biodiversity. The purpose of the research was to study Bubbor Paddas for an educational video of biodiversity. Another objective is to ascertain audience"™s perceptions of the educational videos that have been produced. The research methodology employed was field exploration, employing ethnobiological principles, to assess the Bubbor Paddas. A survey using questionnaires was also conducted to determine perceptions of the video. The making of Bubbor Paddas uses certain tools and processes. There are 25 plant species and one animal species used in making Bubbor Paddas. The 25 plant species belong to the clade or class of eudicots, monocots, magnoliids, and polypodiopsida. The animals used are anchovies from the class Actinopterygii. The educational video was uploaded via YouTube and a duration of 7 minutes, 46 seconds. The video is classified within an appropriate category, as it meets the criteria set forth in the video assessment indicators. Respondents stated that the video quality was good. A total of 69.23% strongly agreed that the Bubbor Paddas educational video provided new knowledge for the audience. The Bubbor Paddas educational video is expected to be an alternative to accommodate the low knowledge of the value of biodiversity.Keywords: Bubbor Paddas, indigenous knowledge, biodiversity value, educational video